Impact of the titania nanostructure on charge transport and its application in hybrid solar cells - Koffman Frischknecht, Alejandro (2018)
Porous titania films are widely studied in a number of optoelectronic applications due to its favorable optical and electronic characteristics. Mesoporous titania thin films (MTTFs) with tunable pore size, pore order, accessibility and crystallinity are of interest in electronic devices due to the potential for optimization of the desired characteristics for charge separation and carrier transport. In this work, several MTTFs were prepared by sol–gel chemistry with different structural properties tuned by post-synthesis thermal treatment. The effect of the structural properties (pore diameter, order and accessibility) on the electrical properties of the material was studied by films fabrication onto a transparent conducting electrode, ITO, such that it enables optoelectronic applications. The performance as photoanode was explored by the fabrication of hybrid polymer (P3HT): titania solar cells. Not only does structural properties affect polymer impregnation inside the titania pores as expected and hence impacts charge separation at the interface, but also the thermal treatment affects crystallinity and the films electronic properties. A more complete picture about the electronic properties of the different MTTFs prepared in this work was studied by mobility measurement by space charge limited current and impedance spectroscopy.